O uso da experimentação como recurso didático no desenvolvimento do trabalho de professores de física no ensino médio - Wesendonk, Fernanda Sauzem [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
We seek this research understand how they operate the different factors involved in the use of experimentation by teachers of Physical Education. For both, we seek to answer the following research question: What factors influence the use of experimentation by teachers of Physical Education? Considering the nature of the information collected and reported in this research, we classify the search as qualitative. As the source for the information-gathering process, we use basically the modality subject, more specifically Physics teachers of Physics teachers of Middle School service in Schools for Basic Edfucation in the Public School System State of the city of Bauru/SP. The instruments for the collection of information in these sources were questionnaires and interviews. The study involved 16 teachers of Physical Education in Middle shools. The procedures for the organization, treatment and analysis of the collected information followed the guidelines from the perspective known as Grounded Theory. The analyses we can say that: (1) the academic training initial influence directly on the frequency of use of experiments by teachers and in how they organize and lead-based activities in this teaching resource; (2) the completion of courses/meeting/process continued training, which have a focus on experimentation, may contribute to the higher incidence of experiments in the shool context; (3) the professional conditions for the development of work teaching of teachers influence the use of experiments in Physics classes; (4) the presence of Curricular Proposal journal of SEE/SP and the SARESP, in the context of the State of São Paulo, influence the choices of the teachers and, consequently, lead to the low frequency of use of experimentation in their classes; (5) the presence of Physics lab or Science in shool and experimentals materials contributes to the more frequent use of experiments in Physics Teaching; (6) the objectives/goals that the...

Buscamos, com esta pesquisa, compreender como operam os diferentes fatores envolvidos na utilização de experimentações por professores de Física do Ensino Médio. Para tanto, procuramos responder o seguinte problema de pesquisa: Que fatores influenciam a utilização de experimentação por professores de Física do Ensino Médio? Considerando a natureza das informações coletadas e indicadas nesta investigação, classificamos a pesquisa como qualitativa. Como fonte para o processo de coelta de informações, utilizamos basicamente a modalidade sujeitos, mais especificamente professores de Física do Ensino Médio em serviço em Escolas de Educação pertencentes à Rede Escolar Pública Estadual da cidade de Bauru/SP. Os instrumentos para a coleta de informações nessas fontes foram questionários e entrevistas. A pesquisa envolveu 16 professores de Física do Ensino Médio dessas escolas. Os procedimentos de organização, de tratamento e de análise das informações coletadas seguiram as orientações da perspectiva conhecida como Teoria Fundamentada. Pelas análises realizadas podemos afirmar que: (1) a formação acadêmica inicial influencia na fequencia da utilização de experimentos pelos professores e no modo como eles organizam e conduzem as atividades baseadas nesse recurso didático: (2) a realização de cursos/encontros/processos de formação continuada, que tenha como foca a experimentação, pode contribuir para a maior incidência de experimentos no contexto escolar; (3) as condições profissionais para o dsenvolvimento do trabalho didático-pedagógico de professores influenciam na utilização de experimentações nas aulas de Física; (4) a presença da Proposta Curricular oficial da SEE/SP e do SARESP, no contexto do Estado de São Paulo, condicionam as escolhas do professor e, consequentemente levam à baixa frequencia de utilização de experimentações em suas aulas; (5) a presença de laboratório de...
The use of experimentation and teaching resource in the development of the work of teachers of Physical Education the Middle
Keywords: Teaching; Ensino; Pesquisa experimental; Didática; Física - Ensino; Ensino médio